PENINGKATAN HASIL BELAJAR DENGAN METODE BERMAIN PERAN PADA MATA PELAJARAN BAHASA INGGRIS DI KELAS IV MI THORIQOTUL FALAH TALANGKEMBAR TAHUN PELAJARAN 2017/2018 - Akhmad Aji Pradana; Annisa Ulfa’atin Sholihah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
English is an international language that is important to learn because English can be used to communicate with any nation. Along with the above, learning English needs to be introduced to students as early as possible. The limited allocation of time in learning English has an impact on the lack of level of student understanding and enthusiasm of students in English subjects, so that the achievement of learning outcomes is also far from the minimum standards of completeness set by the institution. This study aims to increase the level of activity and enthusiasm of students in learning English, improve student learning outcomes in English subjects. This research method uses classroom action research (Action Classroom Research) with a learning approach using a cycle and described using descriptive analysis methods. Qualitatively, namely by observing to obtain student attitudes data during the process of teaching and learning activities (KBM) and teachers in applying methods in learning. While quantitative is to process data in the form of numbers from formative test results in each cycle. Descriptive analysis is intended to explain the recapitulation of qualitative data obtained during KBM. The research subjects were class IV MI Thoriqotul Falah Talangkembar District Montong Tuban Regency, with the number of students 19 children consisting of 10 female students and 9 male students with heterogeneous student abilities. From the results of this study it can be concluded that, the use of role playing methods has an effect on improving student learning outcomes. Recapitulation of the acquisition of the class average of 67.5 at the pre cycle stage, 75.68 in the first cycle, and 77.37 in the second cycle. The number of students completing learning increases each cycle, initially 9 students at the pre-cycle stage, 12 students in the first cycle, and 17 students in the second cycle. Classical completeness also reached the target height of 89.50% at the end of the second cycle, from 43.36% at the beginning of the cycle and 75.68% at the cycle I stage.